Behavioral Interventions to Reduce Infections in Pediatric Long-term Care Facilities: The Keep It Clean for Kids Trial. Issue 2 (3rd April 2018) - Larson, Elaine L.; Murray, Meghan T.; Cohen, Bevin; Simpser, Edwin; Pavia, Marianne; Jackson, Olivia; Jia, Haomiao; Hutcheon, R. Gordon; Mosiello, Linda; Neu, Natalie; Saiman, Lisa
ABSTRACT: Children in pediatric long-term care facilities (pLTCF) represent a highly vulnerable population and infectious outbreaks occur frequently, resulting in significant morbidity, mortality, and resource use. The purpose of this quasi-experimental trial using time series analysis was to assess the impact of a 4-year theoretically based behavioral intervention on infection prevention practices and clinical outcomes in three pLTCF (288 beds) in New York metropolitan area including 720 residents, ages 1 day to 26 years with mean lengths of stay: 7.9–33.6 months. The 5-pronged behavioral intervention included explicit leadership commitment, active staff participation, work flow assessments, training staff in the World Health Organization "'five moments of hand hygiene (HH), " and electronic monitoring and feedback of HH frequency. Major outcomes were HH frequency, rates of infections, number of hospitalizations associated with infections, and outbreaks. Mean infection rates/1000 patient days ranged from 4.1–10.4 pre-intervention and 2.9–10.0 post-intervention. Mean hospitalizations/1000 patient days ranged from 2.3–9.7 before and 6.4–9.8 after intervention. Number of outbreaks/1000 patient days per study site ranged from 9–24 pre- and 9–18 post-intervention (total = 95); number of cases/outbreak ranged from 97–324 (total cases pre-intervention = 591 and post-intervention = 401). Post-intervention, statistically significant increases in HH trends occurred in one of three sites, reductions in infections in two sites, fewer hospitalizations in all sites, and significant but varied changes in the numbers of outbreaks and cases/outbreak. Modest but inconsistent improvements occurred in clinically relevant outcomes. Sustainable improvements in infection prevention in pLTCF will require culture change; increased staff involvement; explicit administrative support; and meaningful, timely behavioral feedback.